2021
DOI: 10.12659/msm.933782
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Birth Defects in Eastern China and the Associated Risk Factors

Abstract: Background This study aimed to survey the overall situation of birth defects (BDs) among citizens of Hangzhou, China, and the risk factors of different BD types. Material/Methods We collected the data of 4349 perinatal infants with BDs in Hangzhou. The potentially associated risk factors of BDs were recorded and logistic regression analysis was used to predict the high incidence of BDs. Results Among all perinatal infants with BDs, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For another, the educational level of pregnant women is often to be considered when exploring the risk factors of BDs. However, some studies indicated that pregnant women with low educational levels were found to be the risk factors for overall BDs (OR = 8.40, 95% CI: 2.17 to 32.52) 63 , while some other studies showed that pregnant women with high educational levels were found to be the risk factors of BDs such as down syndrome 64 . In addition, high family monthly income is also found to be a risk factor for BDs such as syndactyly 64 .…”
Section: Discussionmentioning
confidence: 99%
“…For another, the educational level of pregnant women is often to be considered when exploring the risk factors of BDs. However, some studies indicated that pregnant women with low educational levels were found to be the risk factors for overall BDs (OR = 8.40, 95% CI: 2.17 to 32.52) 63 , while some other studies showed that pregnant women with high educational levels were found to be the risk factors of BDs such as down syndrome 64 . In addition, high family monthly income is also found to be a risk factor for BDs such as syndactyly 64 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that there is no consensus on whether the high maternal education level is a risk factor or a protective factor for BDs. Most scholars indicate that low maternal educational level is a risk factor for BDs (39,44), because it can significantly increase the risk of having a fetus with BDs (OR = 8.40, 95% CI: 2.17-32.52) (45), but other researchers find that high maternal educational level is also a risk factor for BDs, such as DS (11). In this study, it is observed that pregnant women with high education levels were more likely to give birth to a fetus with BDs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that approximately 65.00%-70.00% of BDs are ascribed to complex genetics with unknown factors (2). Several researchers have also shown that the potential associated risk factors of BDs included maternal age, gravidity, parity, monthly income of the family, education level of pregnant women (11), household registration, history of miscarriages, family history of BDs, infection, taking medicine, pesticide exposure, and single/twin pregnancy (12). Therefore, how to effectively prevent BDs has become very urgent and important.…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of BDs might have increased, and approximately 3–5% of births worldwide are affected by BDs ( 2 , 4 ). In China, the prevalence of BD ranges from 0.715 to 19.184% ( 8 ). Recently, increase attention has been paid to BDs in low-income provinces of southwestern China.…”
Section: Introductionmentioning
confidence: 99%